SOCIAL BEHAVIOR OF EARLY CHILDREN IN THE NUSUKAN RAILWAY ENVIRONMENT, SURAKARTA - Afi Zumrotul Fikria; Sri Hartini; Feri Faila Sufa (Journal of Early Childhood Education (JECE), 2021)
Children's social development is how early childhood interacts with peers, adults, and the broader community to adapt. Parents and the environments are figures or models closest to children and become role models for children. This study aimed to determine children's social behavior and the role of the environment on the social behavior of children aged 5-6 years in the Nusukan Surakarta railway environment. This type of research uses descriptive qualitative methods—sampling using a purposive sampling technique. The data analysis technique used the Milles and Huberman model with three stages: data reduction, presentation, and conclusion. The results show that children's social behavior in the Nusukan railway area tends to be active, but some behaviors still need guidance so that children have good social behavior. It is inseparable from family environmental factors, both parents, siblings, peers, or other adults through their environment. Child development is strongly influenced by treatment or parental guidance for children in recognizing various aspects of social life or norms of social life. Social behavior is closely related to children's behavior in adjusting to the rules of society in the surrounding environment. Children obtain social behavior through maturity and learning opportunities from various stimuli provided by their environment.